A complete science-teaching activity from planning to evaluation - Pacis, Jose B. (1974)
This study provides a framework of information to which the teacher may, as the years go by, add the necessary amount of "flesh" in order to complete and round out his skill in teaching science to the young.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Science -- Study and teaching (Secondary).